Acute hepatitis in three patients with systemic juvenile idiopathic arthritis taking interleukin-1 receptor antagonist - Hollister J Roger; Nash S Russell; Narkewicz Michael R; Higgins Gloria; Frankovich Jennifer; Canna Scott; Soep Jennifer B; Dragone Leonard L (BMC, 2009)
Abstract Purpose We investigated the etiology of acute hepatitis in three children with systemic Juvenile Idiopathic Arthritis (sJIA) taking Interleukin-1 receptor antagonist (IL1RA). Methods Laboratory and clinical data for three children with sJIA diagnosed at ages 13 months to 8 years who developed acute hepatitis during treatment with IL1RA were reviewed for evidence of sJIA flare, infection, macrophage activation syndrome (MAS), malignancy, and drug reaction. Results In all patients, hepatitis persisted despite cessation of known hepatotoxic drugs and in absence of known infectious triggers, until discontinuation of IL1RA. Liver biopsies had mixed inflammatory infiltrates with associated hepatocellular injury suggestive of an exogenous trigger. At the time of hepatitis, laboratory data and liver biopsies were not characteristic of MAS. In two patients, transaminitis resolved within one week of discontinuing IL1RA, the third improved dramatically in one month. Conclusions Although sJIA symptoms improved significantly on IL1RA, it appeared that IL1RA contributed to the development of acute hepatitis. Hepatitis possibly occurred as a result of an altered immune response to a typical childhood infection while on IL1RA. Alternatively, hepatitis could have represented an atypical presentation of MAS in patients with sJIA taking IL1RA. Further investigation is warranted to determine how anti-IL1 therapies alter immune responsiveness to exogenous triggers in patients with immune dysfunction such as sJIA. Our patients suggest that close monitoring for hepatic and other toxicities is indicated when treating with IL1RA.